Sufficiently Safeguarded?: Competency Evaluations of Mentally Ill Respondents in Removal Proceedings - Sherman-Stokes, Sarah (2016)
In this Article, I examine the current regime for making mental competency determinations of mentally ill and incompetent noncitizen respondents in immigration court. In its present iteration, mental competency determinations in immigration court are made by immigration judges, most commonly without the benefit of any mental health evaluation or expertise. In reflecting on the protections and processes in place in the criminal justice system, and on interviews with removal defense practitioners at ten different sites across the United States, I conclude that the role of the immigration judge in mental competency determinations must be changed in order to protect the fundamental fairness of the proceeding. Specifically, I propose a central role for mental health professionals, whose expertise, evaluation, and testimony can inform the court and lead to a more thorough and fair decisionmaking process